The Role of Algae in Biofuel Production: Potentials and Challenges for Sustainable Transportation - Dessy Agustina Sari; Moh. Djaeni; Hadiyanto Hadiyanto; Aji Prasetyaningrum (Diponegoro University, 2025)
This study aims to explore the potential of algae for sustainable biofuel production by examining their molecular biology and the use of advanced cultivation techniques. As concerns over greenhouse gas emissions and rising transportation energy costs grow, algae offer a promising alternative for fuel derived from both food and non-food sources. This review looks at the main biological pathways involved in making biofuels from algae. It focuses on species diversity, lipid content, and new technologies like photobioreactors and magnetic nanoparticle harvesting. The results showcase noteworthy advancements in biotechnology and genetic engineering that boost algae productivity and fuel yield, while also critically examining the environmental impacts such as CO2 emissions and water use, as well as the economic and policy challenges through a life cycle analysis. Adopting a global perspective, this review emphasizes the role of international collaboration and technology transfer in overcoming barriers. Conclusion: Algae-based biofuels hold considerable potential for reducing CO2 and supporting sustainable transportation, yet scaling up production and lowering costs remain challenges. Future research should focus on improving integrated biorefinery platforms, exploring CO2 capture, and promoting international partnerships.